Understanding geography 4 - Khoo, Doris; Tham, Yoke Chun Ang Siew Hong (Longman Singapore, 2000)
Understanding Geography 4 is an educational book that introduces key geographical concepts, landscapes, and environmental issues to young students in an accessible and engaging way.